Answer:
<h3>2√3</h3>
Step-by-step explanation:
The standard equation of a circle is expressed as;
(x-a)²+(y-b)² = r² where;
(a, b) is the center of the circle
r is the radius of the circle
Given the equation (x - 7)^2 + (y + 13)^2 = 12
On comparing;
r² = 12
Take the square root of both sides
√r² = √12
r = √12
r = √4*3
r = 2√3
Hence the radius of the circle is 2√3
The answer is f=3. You get this by combining like terms.
None of them because they are not in order
Answer:
Option 3
Step-by-step explanation:
(f/g)(x) = f(x)/g(x)
Since g(x) is in the denominator, it can't be 0.
(Functions is undefined when the denominator = 0)
This fraction becomes undefined when:
-14x² - 1 = 0
14x² = -1
x² = -1/14
So x² should not be -1/14